Late status of Fontan patients with persistent surgical fenestration - Atz, Andrew M; Travison, Thomas G; McCrindle, Brian W; Mahony, Lynn; Quartermain, Michael; Williams, Richard V; Breitbart, Roger E; Lu, Minmin; Radojewski, Elizabeth; Margossian, Renee; Covitz, Wesley; Gersony, Welton M (Journal of the American College of Cardiology, 2011)
This study was undertaken to determine the effects of creating a systemic-to-pulmonary venous atrial-level communication (fenestration) at the time of the Fontan procedure on late outcomes. Fenestrations are frequently performed during Fontan procedures, but late consequences are not well described. Patient characteristics were compared between those with and without surgical fenestration among 536 subjects (mean age 11.9 years) enrolled in the Pediatric Heart Network Fontan Cross-Sectional Study. The status of the fenestration and the association of a currently patent fenestration with health status and measures of ventricular performance were investigated. Fenestration was performed in 361 patients (67%), and frequency differed by year and center (p < 0.001 for each). After adjustment for center, age at Fontan, year of Fontan, and prior superior cavopulmonary surgery, the fenestrated group had shorter length of Fontan hospital stay. At the time of cross-sectional testing 8 ± 3 years after Fontan, the fenestration remained open in 19% of subjects. Among those with confirmed fenestration closure, 59% were by catheter intervention and 1% by surgical intervention, and 40% had apparent spontaneous closure. Compared with those without evidence of a fenestration, subjects with a current fenestration were taking more medications (p = 0.02) and had lower resting oxygen saturation (median 89% vs. 95%, p < 0.001). Functional health status, exercise performance, echocardiographic variables, prevalence of post-Fontan stroke or thrombosis, and growth did not differ by current fenestration status. Surgical fenestration is associated with well-demonstrated early post-operative benefits. This cross-sectional study found few associations between a persistent fenestration and deleterious later outcomes.